2003
DOI: 10.1046/j.1365-2036.18.s1.3.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long‐term administration of rebamipide on Helicobacter pylori infection in mice

Abstract: SUMMARYBackground: It has been suggested that chronic, persistent, uncontrolled inflammations in the stomach could provide the basic step for the beginning of carcinogenesis. One of the potential clinical applications of rebamipide is the inhibition of the immunoinflammatory response in gastric mucosa imposed by Helicobacter pylori. Aim: To determine the implications of long-term rebamipide treatment in H. pylori infection, we studied the underlying moleculo-pathological changes in gastric lesions in mice infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
(94 reference statements)
0
30
1
Order By: Relevance
“…The lack of effect of rebamipide on the Tcell stimulation markers, CD44 and CD62L, suggests that these markers are less sensitive parameters of T-cell stimulation than cytokine secretion, at least in our model. The immuno-stimulatory properties of rebamipide observed in this study are in contrast to the previous studies where an inhibitory effect was observed on immune response, both in vitro [23][24][25][26][27], and in vivo [9,[28][29][30]. This apparent contradiction may be explained by differences in the models used.…”
Section: Discussioncontrasting
confidence: 86%
“…The lack of effect of rebamipide on the Tcell stimulation markers, CD44 and CD62L, suggests that these markers are less sensitive parameters of T-cell stimulation than cytokine secretion, at least in our model. The immuno-stimulatory properties of rebamipide observed in this study are in contrast to the previous studies where an inhibitory effect was observed on immune response, both in vitro [23][24][25][26][27], and in vivo [9,[28][29][30]. This apparent contradiction may be explained by differences in the models used.…”
Section: Discussioncontrasting
confidence: 86%
“…According to Shimakura and Boland [34], under basal condition, gastric epithelial cell line, AGS-the same cell line used in the current experiment-produce LTD 4 as its principal eicosanoid metabolite followed by 6-keto-PGE 1 , LTC 4 , LTB 4 , 12-HETE, TXB 2 , PGF 2α , PGE 2 , 12-HETE, 15-HETE, and PGD 2 , but after stimulation with calcium ionophore, the principal eicosanoid metabolites become 12-HETE, followed by LTB 4 , LTC 4 , PGF 2α , PGE 2 , 6-keto PGF 1α , TXB 2 , LTD 4 , 15-HETE, and PGD 2 , suggesting that 5-LOX might be more active than COX in gastric epithelial cells. Their ability to metabolize AA differed according to cell context and each cell type may have a unique ability to produce PGs, HETEs, LTs, and other related eicosanoids.…”
Section: Discussionmentioning
confidence: 99%
“…Helicobacter pylori infection has been known to be associated with several pathologic alterations in stomach, including chronic gastritis, gastroduodenal ulcer, mucosa-associated lymphoid tissue lymphoma, and gastric adenocarcinoma [1][2][3][4], all of which were pathophysiologically based on chronic persistent gastric inflammations and crossroad between inflammation and carcinogenesis [5]. It has been shown that colonization of H pylori in the gastric mucosa induces a dramatic change in gastric mucosal phospholipid composition and elevates the metabolites of various eicosanoids from epithelial membrane phospholipid, which has been related to inflammatory host responses in infected gastric environment [5,6].…”
Section: Abstract Helicobacter Pylori Red Ginseng 5(s)-hete 5-lmentioning
confidence: 99%
“…Apoptotic abnormality is considered as an important mechanism underlying the development of gastric carcinoma [18,19] and even more crucial than the reproduction of cells of out control [20,21] . The expression of apoptotic signal proteins play different roles in the death of gastric cancer cells.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%